Екологічна приуроченість деревостанів з участю сосни кедрової європейської (Pinus cembra L.) в Українських Карпатах - Sirenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The description of amplitude of a European cedar pine (Pinus cembra L.) rather temperature factor, deposits, exposition and steepness of slopes, height above a sea level, ground are presented.